Extra-Nasopharyngeal Angiofibroma in a Pre-Pubertal Child - Subhro Ganguly; Surendra H Gawarle; Prashant N Keche (Journal of Clinical and Diagnostic Research, 2017)
Nasopharyngeal Angiofibromas (NA) are benign fibro-vascular tumours, predominantly occurring in the region around sphenopalatine foramen of adolescent males. Angiofibromas arising outside nasopharynx are termed as Extra-Nasopharyngeal Angiofibromas (ENA) which often gets misdiagnosed because of its rarity and atypical clinical and biological behaviour. We present a case of angiofibroma of nasal septum in a seven-year-old boy presenting with two months history of left nasal obstruction and occasional nasal bleeding. CECT revealed a contrast enhanced soft tissue mass in left nasal cavity with no extension into the sinuses and nasopharynx. The mass was completely removed by lateral rhinotomy approach and a follow up of ten months showed no recurrence. Histopathology and immunohistochemistry confirmed the diagnosis of angiofibroma. The age of the patient and the location of the tumour make the case exceptionally rare. We conclude that ENA must be taken into consideration in differential diagnosis of unilateral vascular nasal mass, and nasal septum should be taken into account as a potential, yet exceptional site for the tumour. Furthermore the age and gender of the patient should not be given utmost importance for diagnosis of angiofibromas.